KARAKTERISTIK ORGANOLEPTIK DAN FISIKO-KIMIA PRODUK SUI WU’U DENGAN PENAMBAHAN TEPUNG BERAS MERAH (Organoleptic and Physico-Chemical Characteristics of Sui Wu’u Products wuth The Addition of Red Rice Flour) - Rosalia Rosinta; G. E. M Malelak; Arnol E. Manu (Universitas Nusa Cendana, 2026)
Sui wu'u is a pork product typical of the people of Flores (Ngada), East Nusa Tenggara, and has been passed down through generations since ancient times. This dish is made from pork preserved in a unique way using corn flour and salt, then stored in bamboo segments (tuku).This study aims to determine the effect of adding red rice flour on the organoleptic and physicochemical quality of sui wu'u. This study used a Completely Randomized Design (CRD) with 4 treatments and 4 replications. The treatments included P0 (control without red rice flour), P1 (10% red rice flour), P2 (20% red rice flour), and P3 (30% red rice flour) from corn flour. The results showed that the addition of red rice flour significantly affected the color of sui wu'u (P<0.01), where the color changed from bright red to dark red at 30% treatment. Aroma, taste, and tenderness did not experience significant changes (P>0.05). The treatment did not affect pH and water activity (P>0.05), but significantly affected protein content, fat content, fat oxidation and anthocyanin (P<0.01) with a decrease in protein and fat content and an increase in anthocyanin content at the highest treatment (P3). It was concluded that the addition of red rice flour up to 30% had a positive effect on several physico-chemical quality parameters (except protein content) of sui wu'u without significantly changing the organoleptic properties except color.